PIPERAZINE IN PEDIATRIC ASCARIASIS: PHARMACOKINETICS, PHARMACODYNAMICS, AND GLOBAL HEALTH PERSPECTIVES - Mohammed, Othman Mueen; Ismail, Mona Adel; Jasim, Mohannad Hamid; Salih, Thaer Abdulqader; AlHayani, Dhyauldeen Aftan; Hamad, Anas Abdullah (International Journal Multidisciplinary (IJMI), 2025)
Objective:  Currently, Ascaris lumbricoides-induced ascariasis has become a major health burden in the world, especially in low- and middle-income nations and children blacked with such situations. Ascariasis has an impact of more than 1 billion population of the entire world which results in more than 1.3 million disability-adjusted life years (DALYs) per year, mainly because of growth retardation, malnutrition, and children with cognitive performance. Method: This review examines the pharmacokinetics (PK), pharmacodynamics (PD), safety, and clinical efficacy of piperazine in children with accommodation of developmental differences in physiological processes that influence the absorption, distribution, metabolism, and elimination of drugs. Results: Crucial results indicate that a higher digestive availability and quicker intestinal assimilation of piperazine is present in pediatric patients who could reach the effective therapeutic concentrations in the lumen as compared to adults. The pharmacodynamic profile is strong GABAergic effects in nematodes at low systemic exposure in children, which proves its application in the regions with a high prevalence of parasitic worm infestations, mass deworming programs, and among individuals where benzimidazoles use is contraindicated. Novelty: The potential implications of the proposed action on the pharmacology of age specificity in helminth management schemes of control is also quantified within the context of the current review and justifies sustained application of piperazine in age-specific interventions.